Aeroallergen Der p 2 induces apoptosis of bronchial epithelial BEAS-2B cells via activation of both intrinsic and extrinsic pathway. Issue 1 (December 2015) - Lin, Chun-Hsiang; Hong, Yu-Chuan; Kao, Shao-Hsuan
Abstract Background Excessive apoptosis of airway epithelium is reported to induce airway remodeling and inhibited airway epithelium repair is highly associated with development of asthma and chronic obstructive pulmonary disease. Der p 2 is a major allergen derived fromDermatophagoides pteronyssinus and commonly causes airway hypersensitiveness and asthma; however, the connection between Der p 2 and epithelial apoptosis remains unclear. This study was aimed to explore whether Der p 2 induces apoptosis of airway epithelial cells and the underlying mechanisms. Results Our results showed that recombinant Der p 2 (rDP2) inhibited cell growth and induced apoptosis of human bronchial epithelial cell BEAS-2B. Further investigation revealed that rDP2 increased intracellular reactive oxygen species, level of cytosolic cytochrome c and cleavage of caspase-9 and caspase-3. rDP2 also induced activation of p38 mitogen-activated protein kinase (P38) and c-Jun N-terminal kinase (JNK), and triggered proapoptotic signals including decrease of Bcl-2, increase of Bax and Bak, and upregulation of Fas and Fas ligand. In parallel, rDP2 inhibited glycogen synthase kinase 3beta and consequently enhanced degradation of cellular (FADD-like IL-1β-converting enzyme)-inhibitory protein (c-FLIP). Involvement of toll-like receptor (TLR)2 in rDP2-induced apoptosis was also demonstrated using specific small inhibitory RNA. Conclusions Our findings indicate that rDP2 suppresses cell growth and trigger apoptosis of BEAS-2B cells, which may attribute to induction of both intrinsic and extrinsic pathway via TLR2 and P38/JNK signaling and c-FLIP degradation. It suggests that Der p 2 may aggravate respiratory disorders through enhancement of apoptosis and the consequent airway injury.